Inhibition of LRRK2 restores parkin-mediated mitophagy and attenuates intervertebral disc degeneration. Issue 4 (April 2021) - Lin, Jialiang; Zheng, Xuanqi; Zhang, Zengjie; Zhuge, Jinru; Shao, Zhenxuan; Huang, Chongan; Jin, Jie; Chen, Ximiao; Chen, Yu; Wu, Yaosen; Tian, Naifeng; Sun, Liaojun; et al.
Summary: Objective: To elucidate the role of LRRK2 in intervertebral disc degeneration (IDD) as well as its mitophagy regulation mechanism. Methods: The expression of LRRK2 in human degenerative nucleus pulposus tissues as well as in oxidative stress-induced rat nucleus pulposus cells (NPCs) was detected by western blot. LRRK2 was knocked down in NPCs by lentivirus (LV)-shLRRK2 transfection; apoptosis and mitophagy were assessed by western blot, TUNEL assay, immunofluorescence staining and mitophagy detection assay in LRRK2-deficient NPCs under oxidative stress. After knockdown of Parkin in NPCs with siRNA transfection, apoptosis and mitophagy were further assessed. In puncture-induced rat IDD model, X-ray, MRI, hematoxylin-eosin (HE) and Safranin O-Fast green (SO) staining were performed to evaluate the therapeutic effects of LV-shLRRK2 on IDD. Results: We found that the expression of LRRK2 was increased in degenerative NPCs both in vivo and in vitro . LRRK2 deficiency significantly suppressed oxidative stress-induced mitochondria-dependent apoptosis in NPCs; meanwhile, mitophagy was promoted. However, these effects were abolished by the mitophagy inhibitor, suggesting the effect of LRRK2 on apoptosis in NPCs is mitophagy-dependent. Furthermore, Parkin knockdown study showed that LRRK2 deficiency activated mitophagy by recruiting Parkin. In vivo study demonstrated that LRRK2 inhibition ameliorated IDD in rats. Conclusions: The results revealed that LRRK2 is involved in the pathogenesis of IDD, while knockdown of LRRK2 inhibits oxidative stress-induced apoptosis through mitophagy. Thus, inhibition of LRRK2 may be a promising therapeutic strategy for IDD.